PELATIHAN PENGGUNAAN BAHAN AJAR BERBANTUAN FLIP PDF DAN PRESENTASI DENGAN MENTIMETER.COM - Amnie, Erlida; Pathoni, Haerul; Pujaningsih, Febri Berthalita; Astalini, Astalini; Susanti, Nova (Jurnal Abdi Insani, 2024)
Education and learning globally has undergone a change from an era focused on direct learning to blended learning. The pandemic has also contributed to the pattern of learning that was originally online and then directed to return to semi-online offline learning. online. This learning adaptation phenomenon is also felt in the learning process of high school teachers in Tanjung Jabung Timur Regency, Jambi Province. East Tanjung Jabung Regency, Jambi Province. Teachers have their own challenges to design learning activities that learning activities that can restore learners' interest and attention when attending face-to-face classes. Based on these conditions, a service activity was carried out that focused on training on the use of Flip PDF as a teaching material maker application and equipped with the use of mentimeter.com as one of the options for making interactive presentation media in learning. making interactive presentation media in learning. This training conducted at SMA N 8 Tanjung Jabung Timur. Teachers are given training on the use of Flip PDF as an electronic teaching material in learning in the first session. Teachers also gained experience in creating interactive presentation media through the site mentimeter.com. After participating in the activities, teachers have additional skills related to making teaching materials and interactive presentation media and interactive presentation media during the learning process. Training in the use of Flip PDF and Mentimeter can be an important step in improving the quality of learning in improving the quality of learning in the digital era. This approach gives educators a powerful tool to create a more interactive and engaging learning experiences that are more interactive and engaging. Thus, efforts to improvequality of education can be continuously improved through the effective use of technology.